Inclusive Environments: Home, Work, Public Spaces, Technology, and Specialty Environments within Occupational Therapy Practice. (American Journal of Occupational Therapy)
This position statement describes the role and importance of occupational therapy practitioners in integrating inclusive environments into their professional services and into their underlying science. Primary documents that define the occupational therapy profession clearly support its role in creating and ensuring inclusive environments. AOTA's updated position statement describes the role and importance of occupational therapy practitioners in integrating inclusive environments into their professional services and into their underlying science.